2013
DOI: 10.4236/crcm.2013.23053
|View full text |Cite
|
Sign up to set email alerts
|

Retropharyngeal emphysema: An unusual aetiology—A case report and literature review

Abstract: Introduction: Retropharyngeal emphysema is a potentially life threatening condition which may require urgent diagnosis and intervention. It has been documented to occur following trauma to the aerodigestive tract and is usually accompanied by subcutaneous emphysema of the cervical region. This condition may be complicated by mediastinal emphysema and pneumomediastinum. Foreign body ingestion is quite common in little children and in this environment; a cultural practice is for mothers or other caregivers to at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Cervical emphysema is usually seen in association with penetrating trauma, infections from gas forming organisms, or cases in which a breach in the integrity of the upper aerodigestive tract has occurred [1,2]. In cases where these are not clinically evident, the term spontaneous cervical emphysema is used.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cervical emphysema is usually seen in association with penetrating trauma, infections from gas forming organisms, or cases in which a breach in the integrity of the upper aerodigestive tract has occurred [1,2]. In cases where these are not clinically evident, the term spontaneous cervical emphysema is used.…”
Section: Discussionmentioning
confidence: 99%
“…Other causes include pulmonary conditions such as bronchiolitis, pneumonia and asthma or rupture of pulmonary bulla [1,3,4]. Surgically induced spontaneous emphysema has also been reported in cases of tooth extraction and gastrointestinal surgery in which the primary operated site is not within the cervical region [2,5]. Dekel et al reported that the primary complaints of subcutaneous emphysema were neck swelling which may be associated with pain and also obstructive symptoms depending on the extent of the disease as in this case [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presentation may vary depending on the cause of RAC, amount or site where most air accumulates. As the air dissects through various fascial planes, the patient may present with severe sore throat, odynophagia, dysphagia, dysphonia, dyspnoea, generalised neck pain, and neck swelling (13,15) . The onset can be from hours up to days (14) .…”
Section: Repeat Cervical Radiograph Showing Near-complete Resolution ...mentioning
confidence: 99%